Drama technique and paradoxes in the Sophocles’ prologues (Minerva, 2018)
This paper analyses four prologues among the extant tragedies of Sophocles (Ajax, Antigone, Oedipus Rex and Oedipus at Colonus) and studies some features of the drama technique employed by the author. These elements, which in some cases we may see as “paradoxical”, confirm the importance of the prologue as the first part of the tragedy. It has, as its main function, to expose the plot at the beginning of the tragedy in front of the viewers that need this information. The paper offers a classification of regular paradigms in the composition of these four prologues, which present common features but that can be changeable according to each tragedy.
Keywords: Sophocles; prologues; drama technique